Search for heavy resonances that decay into a vector boson and a Higgs boson in hadronic final states at √s=13TeV - KAYA, MİTHAT (My University, 2017)
© 2017, CERN for the benefit of the CMS collaboration.A search for heavy resonances with masses above 1TeV, decaying to final states containing a vector boson and a Higgs boson, is presented. The search considers hadronic decays of the vector boson, and Higgs boson decays to b quarks. The decay products are highly boosted, and each collimated pair of quarks is reconstructed as a single, massive jet. The analysis is performed using a data sample collected in 2016 by the CMS experiment at the LHC in proton-proton collisions at a center-of-mass energy of 13TeV, corresponding to an integrated luminosity of 35.9fb-1. The data are consistent with the background expectation and are used to place limits on the parameters of a theoretical model with a heavy vector triplet. In the benchmark scenario with mass-degenerate W′ and Z ′ bosons decaying predominantly to pairs of standard model bosons, for the first time heavy resonances for masses as high as 3.3TeV are excluded at 95% confidence level, setting the most stringent constraints to date on such states decaying into a vector boson and a Higgs boson.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous); B2G; CMS; Diboson; Hadronic; Higgs; VH